ChemInform Abstract: One‐Pot Mechanosynthesis of Aromatic Amides and Dipeptides from Carboxylic Acids and Amines. Issue 16 (28th March 2013) - Strukil, Vjekoslav; Bartolec, Boris; Portada, Tomislav; Dilovic, Ivica; Halasz, Ivan; Margetic, Davor
Abstract Environmentally friendly one‐pot synthesis of amides such as (III) and (X), bis‐amides (V) and (VIII) and dipeptides (XIII) by mechanochemical carbodiimide‐mediated coupling of carboxylic acids and amines is reported.